Silencing of Fused Toes Homolog (FTS) Increases Radiosensitivity to Carbon-Ion Through Downregulation of Notch Signaling in Cervical Cancer Cells - D.S., Prabakaran; Chaturvedi, Pankaj Kumar; Shimokawa, Takashi; Kim, Ki-Hwan; Park, Woo-Yoon (Frontiers in Oncology, 2021)
We investigated the effects of Carbon ion (C-ion) alone or in combination with fused toes homolog (FTS) silencing on Notch signaling in uterine cervical cancer cell lines (ME180 and CaSki). In both cell lines, upon irradiation with C-ion, the expression of Notch signaling molecules (Notch1, 2, 3 and cleaved Notch1), -secretase complex molecules and FTS was upregulated dose-dependently (1, 2 and 4 Gy). However, overexpression of these molecules was attenuated by FTS silencing. The spheroid formation, expression of stem cell markers (OCT4A, Sox2 and Nanog) and clonogenic cell survival were reduced by the combination as compared to FTS silencing or C-ion irradiation alone. Additionally, immunoprecipitation and immunofluorescence assay revealed interaction and co-localization of FTS with Notch signaling molecules. In conclusion, FTS silencing enhances the radio-sensitivity of the cervical cancer cells to C-ion by downregulating Notch signaling molecules and decreasing the survival of cancer stem cells.